The Impact of Peroxisomes on Cellular Aging and Death - Manivannan, Selvambigai; Scheckhuber, Christian Q.; Veenhuis, Marten; van der Klei, Ida J. (Frontiers in Oncology, 2012)
Peroxisomes are ubiquitous eukaryotic organelles, which perform a plethora of functions including hydrogen peroxide metabolism and β-oxidation of fatty acids. Reactive oxygen species produced by peroxisomes are a major contributing factor to cellular oxidative stress, which is supposed to significantly accelerate ageing and cell death according to the free radical theory of ageing. However, relative to mitochondria, the role of the other oxidative organelles, the peroxisomes, in these degenerative pathways has not been extensively investigated. In this contribution we discuss our current knowledge on the role of peroxisomes in ageing and cell death, with focus on studies performed in yeast.